Cities and climate change : responding to an urgent agenda - Hoornweg, Daniel (Urban development series., 2011)
Introduction : cities and the urgent challenges of climate change -- Greenhouse gas emission baselines for global cities and metropolitan regions / C.A. Kennedy ... [et al.] -- A comparative analysis of global city policies in climate change mitigation : London, New York, Milan, Mexico City and Bangkok / E. Croci, S. Melandri and T. Molteni -- GHG emissions, urban mobility and efficiency of urban morphology / A. Bertaud, B. Lefevre and B. Yuen -- The role of institutions, governance and planning for mitigation and adaptation by cities / H. Bulkeley ... [et al.] -- Viral governance and mixed motivations : how and why U.S. cities engaged on the climate change issue, 2005-2007 / T. Warden -- Urban heat islands : sensitivity of urban temperatures to climate change and heat release in four European cities / M. McCarthy and M. Sanderson -- Adapting cities to climate change : opportunities and constraints / D. Heinrichs ... [et al.] -- A conceptual and operational framework for pro-poor asset adaptation to urban climate change / C. Moser -- Epilogue: perspectives from the 5th Urban Research Symposium -- Appendix: abstracts of papers not included in printed version.